STRATEGI MENGATASI PEMBIAYAAN MURABAHAH BERMASALAH PADA PT.BPRS KABUPATEN NGAWI (PERSERODA) KANTOR KAS GENENG - Dwi Wahyuni, Melli (Fakultas Ekonomi Bisnis Islam, 2024)
Financing is funding provided by one party to another to protect a previously agreed investment. Providing clients with access to capital for investment purposes in accordance with Islamic sharia law is what Islamic financial institutions refer to as financing. In the Islamic financial system, a purchase and sale transaction known as murabahah is one way to finance a project. Although the profit-sharing system is the main selling point of Islamic banking, the term